ZnO and rare earth nanoparticles embedded in SiO2 matrix (ZnO-nc: Eu3+SiO2) - Koh, Amelia Jiamin (2014)
This report covers the study of the development of Zinc Oxide nanocrystals (ZnOnc) doped with Europium (III) Nitrate embedded in SiO2 matrix. The thin films have been developed using sol-gel methods based on previous studies. The objectives are to verify the formation of ZnO-nc and thereafter, optimize the energy transfer process of excited ZnO-nc emission to overlap with the absorption band of Eu3+. Emission intensity from ZnO-nc are recorded using photoluminescence (PL). The optimization process of developing Eu3+ doped ZnO-nc is carried out through varying of time given for gelation during sol-gel process, dopant composition in the matrix, as well as annealing environment. It is conclusive that the optimum dopant concentration of Eu3+ was also found to be between 10-15%. Optimal annealing environment is set to be at 450oC, accompanied with a combination of Rapid Thermal Processing and post-annealing procedures. The following findings are in light of increased interest pertaining to ZnO-nc and its applications the optoelectronic industry which comprises of light emitting displays as well as UV photodetectors.